REIMAGINING TEACHER EDUCATION FOR FUTURE CLASSROOMS - Torkis Dalimunthe (PT Rahis Cendekia Indonesia, 2023)
The rapid evolution of digital technologies, shifts in student learning preferences, and the growing complexity of 21st-century education demand a rethinking of traditional teacher education models. This study explores how teacher education programs are adapting—or failing to adapt—to the emerging needs of future classrooms. Employing a qualitative descriptive approach, data were gathered through interviews, document analysis, and limited classroom observations at selected teacher training institutions. The findings reveal five major themes: uneven digital integration, inconsistent implementation of student-centered pedagogy, challenges in practicum experiences, limited development of 21st-century skills, and varied levels of institutional readiness. While there is a shared understanding of the importance of innovation, practical transformation remains constrained by systemic and structural barriers. The study concludes that meaningful reform in teacher education requires not only updated curricula but also a broader shift in institutional culture, policy alignment, and professional mindset. These changes are essential for preparing educators capable of leading dynamic, inclusive, and future-oriented classrooms.